PENGARUH KINERJA USAHA KULINER DENGAN INKLUSI KEUANGAN SEBAGAI VARIABEL MODERASI - Adha, Nur; Mustari, Mustari; Ampa, Andi Tenri; Dinar, Muhammad; Rahmatullah, Rahmatullah (Universitas Khairun, 2024)
Involving monetary consideration as a mediator variable, this study expects to decide what financial technology and financial literacy affect the culinary business performance in Makassar's Rappocini Region. Perceptions, interviews, and the conveyance of surveys to 120 respondents-an example looked over the current populace were utilized to gather information for the review. This study fits the portrayal of a quantitative illustrative review. Primary Condition Displaying (SEM), a multivariate factual examination approach, is the information investigation technique used to explain the synchronous straight associations between perceptible factors (markers) and idle factors (undetectable factors). For this examination, SmartPLS 4.0 devices are utilized.